Clinical characterization and management of persons with comorbid epilepsy and depression: an expert opinion paper - Sampogna, Gaia; Brugnoli, Roberto; Didato, Giuseppe; Elia, Maurizio; Ferlazzo, Edoardo; Serafini, Gianluca; Vatti, Giampaolo; Volpe, Umberto; Villani, Flavio; Sani, Gabriele (Frontiers in Pharmacology, 2025)
IntroductionMedical conditions related to the nervous system affects 3.4 billion individuals worldwide and are collectively ranked as the leading cause of disability-adjusted life years (DALYs). Epilepsy is listed among the ten conditions with the highest age standardized DALYs, while depression is expected to become the first cause of disability for mental disorders by 2030. Persons with epilepsy have a higher risk of developing depression, and vice versa. Epilepsy and depression both can influence individual’s personal functioning, social activities and can increase the risk of sudden epileptic attacks. Depression is probably the most frequent psychiatric comorbidity reported in patients with epilepsy. Several studies have highlighted a bidirectional association between depression and epilepsy.MethodsThe present mini-review is based on expert meetings held in the period May-September 2024. A panel of expert clinicians, working in the field of epilepsy and of clinical psychiatry have been invited to participate, due to their experience and expertise in the topic. Panel members, under the guidance of two senior experts, have identified the relevant topics to be analyzed, discussed and commented.ResultsIncluded studies dealt with the historical perspective on epilepsy and depression; the complexity of diagnostic and clinical comorbidity between epilepsy and depression; the assessment tools for screening for depression in patients with epilepsy.DiscussionThe clinical condition of patients suffering from comorbid depression and epilepsy represents a challenge for neurologists and psychiatrists. Therefore, the management of comorbid epilepsy and depression requires a detailed clinical characterization of each individual case in order to develop an integrated and personalized management plan.